Pendampingan Strategi Penetapan Harga Berdasarkan Perminataan Pasar Pada UMKM Dimsum Nyoo - Laras Hinda Mulia Fadjri; Hafifah Aisya Putri Sabiya; Annisa Aulia Aryani; Pupung Purnamasari (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
This devotions aims to assist small and medium enterprises (MSMEs) Dimsum Nyoo in determining pricing strategies based on market demand. The methodology used is a qualitative descriptive approach, based on observations and interviews with business leaders. The results of the study indicate that pricing strategies based on cost of goods sold (COGS) and market analysis can build customer loyalty. Despite fluctuating raw material prices, Dimsum Nyoo managed to maintain stable quality and prices, thus contributing to its growth. These results highlight the importance of adaptive pricing to support the sustainability of MSMEs in a competitive market.